1987
DOI: 10.1177/00220345870660050601
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Action of New, Proprietary Lining Cements

Abstract: The antibacterial activity of innovative, commercial lining cements was investigated. A liner which contains calcium hydroxide and is polymerized by visible light (Prisma VLC Dycal) and a glass-ionomer lining cement (GC lining cement) were compared with two more established lining cements (Advanced Formula II Dycal and Life). Antibacterial activity and hemolysis-like agar change at 24, 48, and 72 hours were measured on blood agar plates inoculated with Streptococcus mutans KPSK 2 (serotype c), Lactobacillus ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
4

Year Published

1991
1991
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 12 publications
1
31
0
4
Order By: Relevance
“…Previous studies have suggested that pH may influence a material's solubility [Yoshida et al, 1998] and material pH may also help to determine the antibacterial effect. For example, GICs have an acid pH at set and have a pronounced effect on S. mutans up to 2 days after setting [McComb and Ericson, 1987]. The antibacterial activity of GICs has been attributed to the fluoride release and acidic pH [DeSchepper et al, 1989a, b].…”
Section: Bacterial Growthmentioning
confidence: 99%
“…Previous studies have suggested that pH may influence a material's solubility [Yoshida et al, 1998] and material pH may also help to determine the antibacterial effect. For example, GICs have an acid pH at set and have a pronounced effect on S. mutans up to 2 days after setting [McComb and Ericson, 1987]. The antibacterial activity of GICs has been attributed to the fluoride release and acidic pH [DeSchepper et al, 1989a, b].…”
Section: Bacterial Growthmentioning
confidence: 99%
“…1990Forsten. , 1994, Studies have in dicated that glass ionomer cements and fluoride-releasing composite resins have the ability to inhibit secondary caries at the restoration margin [Donly and Gomez, 1994;GarciaGodoy and Jensen, 1990;Griffin et ah, 1992;Jensen et ah, 1991;Tysowsky et ah, 1988;Zimmerman et ah, 1984], Fur thermore, there appears to be an immediate reduction of bacteria adjacent to fluoride-releasing materials [Berg et ah, 1990;DeSchepper et ah, 1989;McComb and Ericson, 1987]. Not only would secondary caries be reduced at resto ration margins, but the adjacent interproximal tooth could also benefit from constant fluoride release.…”
mentioning
confidence: 99%
“…Bacteriostatic properties possessed by the material itself are regarded as a further benefit of glass-ionomer cements [Tobias et al. 1985: McComb and Ericson. 1987: Scherer et al.…”
mentioning
confidence: 99%